2014
DOI: 10.1037/a0034399
|View full text |Cite
|
Sign up to set email alerts
|

Does observed controlling teaching behavior relate to students’ motivation in physical education?

Abstract: Self-determination theory (SDT) has served as a theoretical framework for considerable research on teaching behavior and student motivation. The majority of studies have focused on need-supportive teaching behavior at the expense of need-thwarting teaching behavior (i.e., the "dark side" of teaching). The goal of the present study was to examine motivational dynamics involved in controlling teaching behavior in the context of physical education (PE). The majority of studies on observed teaching behavior were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
127
2
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(167 citation statements)
references
References 62 publications
18
127
2
9
Order By: Relevance
“…When frustrated, the needs would manifest in feelings of pressure (autonomy need frustration), inferiority and failure (competence need frustration), and loneliness and alienation (relatedness need frustration). We note that whereas Bartholomew, Ntoumanis, Ryan, Bosch, et al (2011) and used the term need thwarting to reflect students' personal feelings, we prefer, consistent with other work (e.g., De Meyer et al, 2014;Vansteenkiste & Ryan, 2013), to use the term need frustration. This is because the term need frustration more closely reflects students' personal experiences (in the same way as need satisfaction does), whereas the term need thwarting is used in reference to contextual features that undermine students needs.…”
Section: Need Satisfaction and Need Frustrationmentioning
confidence: 83%
See 1 more Smart Citation
“…When frustrated, the needs would manifest in feelings of pressure (autonomy need frustration), inferiority and failure (competence need frustration), and loneliness and alienation (relatedness need frustration). We note that whereas Bartholomew, Ntoumanis, Ryan, Bosch, et al (2011) and used the term need thwarting to reflect students' personal feelings, we prefer, consistent with other work (e.g., De Meyer et al, 2014;Vansteenkiste & Ryan, 2013), to use the term need frustration. This is because the term need frustration more closely reflects students' personal experiences (in the same way as need satisfaction does), whereas the term need thwarting is used in reference to contextual features that undermine students needs.…”
Section: Need Satisfaction and Need Frustrationmentioning
confidence: 83%
“…Support for the existence of a specific dark pathway was obtained in the domains of sports (Bartholomew, Ntoumanis, Ryan, Bosch, et al, 2011;Stebbings, Taylor, Spray, & Ntoumanis, 2012), work (Gillet, Fouquereau, Forst, Brunault, & Colombat, 2012), and health (Verstuyf, Vansteenkiste, Soenens, Boone, & Mouratidis, 2013). However, few studies in the educational literature have examined the dark pathways involved in students' motivation (De Meyer et al, 2014). The present study aimed to fill this gap by investigating a theoretically driven model involving a bright path from perceived autonomy support via need satisfaction to optimal motivational functioning and a dark pathway from perceived controlling teaching via need frustration to maladaptive motivational dynamics in the context of PE.…”
mentioning
confidence: 96%
“…Contrary to autonomy-supportive behaviors, controlling interpersonal behaviors (i.e., a coercive and authoritarian way to pressure people to behave in a specific way) have been found to negatively predict autonomous motivation (e.g., Blanchard et al 2009). In addition, recent studies have shown that controlling behaviors were positively associated with controlled motivation (e.g., Assor et al 2005;De Meyer et al 2014). Teachers and supervisors should thus constantly promote, through autonomy-supportive behaviors rather than controlling behaviors, individuals' autonomous motivation to increase their wellbeing.…”
Section: Engagementmentioning
confidence: 96%
“…Thus, in a final study we tested the effects of motivational prosody on controlled (via perceived pressure) and autonomous (via perceived support) motivational states in a school context. Previous studies suggest that motivational climates created by influential figures such as teachers are important in a school setting (e.g., Chirkov & Ryan, 2001;De Meyer et al, 2013;Soenens & Vansteenkiste, 2005), and that important figures influence how children experience and relate to their peers (e.g., Jennings & Greenberg, 2009). …”
Section: Studymentioning
confidence: 99%